Skuteczność reklam społecznych w oddziaływaniu na system aksjo-normatywny - Dmitruk, Joanna; Krzyżanowska, Krystyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The ongoing changes in modern societies and constant build-up of information have caused that compared to colourful and screaming commercial advertisements present everywhere you can see social advertisements and campaigns appearing more and more frequently. Social advertisement focuses on the most important problems in society and there are a lot of difficulties between good understanding and appropriate reactions on this kind of advertisements. Because of this fact, we can say that social advertisement is trying to override barriers of public debate on difficult, shy and taboo themes such as illnesses, addictions or social help. But social advertisement’s biggest challenge is to provoke attitudes and behaviours socially desired. Social advertisement efficiency surveys shows that there aren’t many social advertisements that cause a change or provoke attitudes and behaviours socially desired